Effect of firm complexity on corporate report readability of NGX30 firms - Atawodi-Alhassan, Ojochogwu Winnie; Abdullahi, Aliyu Ahmed; Badara, Mu'azu Saidu; Mamman, Salisu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: This study investigates the effect of firm complexity on the readability of the annual reports of the top 30 listed public firms by market capitalization in the Nigerian Exchange Group. Methodology: The study employs a random effects panel regression analysis on a sample of 178 firm-year observations covering the period of 2012 to 2023. Readability is measured using the Fog index of readability, and firm complexity is operationalized through the number of geographic segments, growth potential, firm size, and firm age. Results and Conclusion: Results from the analysis reveal that firms with a higher number of geographic segments and greater firm age exhibit a statistically significant relationship with a higher Fog index, indicating lower readability. In contrast, firms with higher growth potential and larger sizes are associated with significantly lower Fog index scores, suggesting that such firms produce more readable disclosures. These results lead to the conclusion that the effect of firm complexity on readability relies on the incentives to the firm. Implication of findings: The implication is that firm complexity shapes readability in ways that reflect direct reputation and growth benefits to the firm, with the adverse effects of complexity being mitigated when such benefits are present. As such, recommendations are made for the creation of policies that address low readability where firms are not inherently motivated to produce readable reports.